Predictive factors for cancer treatment delay in an underserved urban population. Issue 28 (1st October 2022) - Sheni, Risha; Qin, Jiyue; Viswanathan, Shankar; Castellucci, Enrico; Mehta, Vikas
Abstract : 136 Background: Incremental delays in time to treatment initiation (TTI) have been shown to cause a proportional, independent increased risk of disease specific mortality for breast cancer, colorectal cancer (CRC), head and neck (HNC), non-small cell lung cancer (NSCLC) and pancreatic cancer. Delays can partly be attributed to increasingly complex workup with modern imaging, genomic and multidisciplinary/multimodality treatments. However, studies suggest delays are associated with racial and socioeconomic disparities, implicating a target for addressing inequity. Given Montefiore Medical Center (MMC) serves a racially diverse, socioeconomically challenged population, we sought to evaluate associations between patient factors and TTI to identify those associated with delay. Methods: Retrospective cohort study at an urban community-based academic center of patients diagnosed with or referred for curative intent treatment of breast cancer, CRC, HNC, NSCLC and pancreatic cancer at MMC from January 2019 to December 2021. Variables of interest included tumor stage, primary treatment modality, median household income, Charlson Comorbidity Index (CCI) score, tobacco use, insurance type, language preference and inpatient (IP) admission or emergency room visit 30 days prior to diagnosis. Results: A total of 2543 patients (F = 1755, M = 788) were identified (mean age 63.4 ± 13.4). The median TTI was 25 days (6, 44 IQR). Factors associated with TTI delay were assessed using logistic regression (Table). Patients who were treated outpatient, and not admitted 30 days prior to diagnosis, experienced increased delay for CRC (OR 2.82) and NSCLC (2.11). Higher CCI score was associated with delay for HNC (2.63) and NSCLC (1.75). For breast cancer, uninsured and Spanish-speaking patients (1.79) were subjected to increased TTI. Conclusions: This study identifies predictors and opportunities for addressing delay and health inequity while improving survival. IP admission 30 days before diagnosis was associated with timely TTI for CRC and NSCLC. Other factors predictive of delay included CCI score in HNC and NSCLC, and insurance type and preferred language in breast cancer.Logistic regression assessing factors associated with TTI delay, stratified by cancer. Cancer (Number of patients, %) Breast (1120, 44.0%) CRC (507, 19.9%) HNC (296, 11.6%) NSCLC (412, 16.2%) Pancreatic (208, 8.2%) Inpatient 30 Prior to Diagnosis OR (95% CI) 2.12 (0.97-4.63) 2.82 (1.71-4.66) 2.02 (0.93-4.37) 2.11 (1.31-3.39) 0.77 (0.38-1.56) Charlson Comorbidity Index Score OR (95% CI) 0.995 (0.65-1.52) 1.31 (0.91-1.88) 2.63 (1.04-6.66) 1.75 (1.14-2.71) N/A Private Insurance vs Uninsured OR (95% CI) 0.44 (0.21-0.93) N/A N/A N/A 0.56 (0.1-3.26) Spanish-speaking (95% CI) 1.79 (1.21-2.67) 0.76 (0.4-1.45) 1.77 (0.85-3.68) N/A N/A Age OR (95% CI) 0.99 (0.97-0.996) 0.99 (0.98, 1.01) 1.001 (0.98-1.02) 0.997 (0.98-1.02) 0.95 (0.91-0.98)